Burnout, help seeking, and perceptions of psychological safety and stigma among National Collegiate Athletic Association coaches - Slowiak, J. M.; Osborne, R. R.; Thomas, J.; Haasan, A. (International Sport Coaching Journal, 2025)
Sport coaches face unique work-related demands that, over time, can lead to negative well-being outcomes, such as burnout. The link between burnout and mental health is supported in the literature, and public stigma around mental health has been identified as a prominent barrier to seeking help. The aim of this study was to investigate how burnout and help-seeking attitudes of National Collegiate Athletic Association coaches are impacted by psychological safety and public stigma associated with seeking help. A sample of 187 National Collegiate Athletic Association coaches participated in a cross-sectional online survey and reported sociodemographic and job-related characteristics, public stigma, self and team psychological safety, burnout, and attitudes toward help seeking. Regression-based mediation analyses revealed that greater psychological safety predicted lower levels of exhaustion and disengagement as well as more positive help-seeking attitudes. In addition, public stigma partially mediated the influence of psychological safety on exhaustion and disengagement and fully mediated the relationship between psychological safety and help-seeking attitudes. No differences in exhaustion, disengagement, and help-seeking attitudes among National Collegiate Athletic Association coaches across Divisions I, II, and III were observed. Findings lend support for intervention development to increase psychological safety as a burnout management strategy as well as to reduce public stigma associated with help seeking.